Late atypical eclampsia: unusual involvement with proteinuria, but without hypertension - Rodríguez Kadota, Liliana (2024)
A 27-year-old primigravida patient without a relevant medical history and appropriate prenatal control received attention for vaginal delivery at 39 weeks of gestation. One -hour later, she experienced holocranial headache with right predominance, treated with anti-inflammatories and muscle relaxants by the indication of a neurologist. Hours after her discharge, on the third day post-partum, she developed bilateral tonic-clonic seizures.. Following a urine test in the emergency room with proteinuria (+) in a dipstick, we tested 24-hour protein count in 1094 mg (normal values 0-140). Magnetic resonance with contrast at admission was normal. She received Phenytoin and Magnesium Sulfate during her hospitalization. The evolution was favorable, and he was discharged at five days with ambulatory controls in the medical office without headache, proteinuria, and/or hypertension.